ACTIVITY OF BAY LEAF EXTRACT (Eugenia polyantha) AS ANTI-INFLAMMATORY IN WHITE RAT (Rattus norvegicus) - Kusumastuti, Ida Ayu Nadia; Jaya, Made Krisna Adi (Journal Pharmaceutical Science and Application; Vol 4 No 1 (2022): Journal Pharmaceutical Science and ApplicationDO - 10.24843/JPSA.2022.v04.i01.p04, 2022)
Background : Inflammation is the body's defense response against foreign body invasion, tissue injury, or both caused by microorganisms, mechanical trauma, chemical compounds, and physical factors. Anti-inflammatory agents can be used to treat inflammation. Bay leaves are one example of a plant that can be used. Ethanol extract and water extract of a bay leaf can be anti-inflammatory because they contain flavonoids.   Objectives : The purpose of this study was to see how effective ethanol extract and aqueous extract of bay leaf were as anti-inflammatory agents in mice . Methods : This study employs a systematic literature review approach, descriptive qualitative research, and library research. Results : The most efficacious dose was 150 mg/kg BW at a 70 percent concentration and at an 80 percent concentration for ethanol extract of bay leaves, and 50 mg/kg BW for the aqueous extract of bay leaves. Conclusion : Based on the results of this study, it can be concluded that bay leaf (Eugenia polyantha) ethanol extract and aqueous extract have anti-inflammatory activities Keywords : Anti-inflammatory, Bay Leaf, Diclofenac sodium, Ethanol Extract, Aqueous